The Influence of Mother Tongue on Communication Skills of Media Practitioners in Kano State, Nigeria. - Liman, Abba; Usman, Baba Jimeta; Abdulhamid, Mustapha (NIU Journal of Humanities, 2017)
This work provides handful themes on areas where attention should be given in other to curtail the transference of phonological attributes of the broadcaster’s mother tongue to that of English language during programmes broadcast in Radio. The population of the study was the ensemble of Radio Broadcasters in Kano state, which were 73. A census of the population served as respondents upon whom the research instrument (questionnaire) was administered. Simple percentages and frequency distribution tables were employed in analysing the data. The studies revealed that majority of the respondents were of the opinion that Nigerian radio broadcasters were affected by mother tongue interference in the course of their programmes. Analysis from the study further revealed that majority of the respondents agree that most Nigerian radio broadcasters are not grounded in the phonological structures of English language, hence cannot pronounce most words properly. The study concluded that this mother tongue interference has hindered many radio broadcasters from external exposure. They should take some extra training in the phonological structures of English language and learn the act of proper pronunciation in order to boost the credibility of the profession. Keywords: Mother Tongue, Broadcasting, Radio.